2021
DOI: 10.1055/s-0041-1739356
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus Rectovaginal Colonization and Resistance Patterns in HIV-Positive Compared to HIV-Negative Pregnant Patients

Abstract: Objective The objective of our study is to determine if human immunodeficiency virus (HIV)-positive pregnant patients have a higher rate of group B streptococcus (GBS) rectovaginal colonization compared with HIV-negative pregnant patients. Methods Our study is a multi-site retrospective study performed at Ochsner Louisiana State University-Health Shreveport and Monroe campuses including patients who delivered between December 2011and June 2019. Rates of GBS rectovaginal colonization between HIV-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Differences in serotype distribution are reported among pregnant women worldwide [64]. Although overall GBS colonization rate was similar, some studies reported differences in serotype distribution between WLWH and HIV-uninfected pregnant women [65,66] with higher rate of colonization by more virulent serotypes reported in different settings in HIC and LMIC [65,67].…”
Section: Upcoming Vaccine: Maternal Group B Streptococcus Vaccinationmentioning
confidence: 98%
“…Differences in serotype distribution are reported among pregnant women worldwide [64]. Although overall GBS colonization rate was similar, some studies reported differences in serotype distribution between WLWH and HIV-uninfected pregnant women [65,66] with higher rate of colonization by more virulent serotypes reported in different settings in HIC and LMIC [65,67].…”
Section: Upcoming Vaccine: Maternal Group B Streptococcus Vaccinationmentioning
confidence: 98%